Ideological indoctrination through propaganda in educational institutions in Romania - Farcaș, Ana-Daniela (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales, 2025)
Political propaganda has often been introduced into educational institutions with the aim of instilling a set of values and a specific mindset in the minds of pupils or students. This phenomenon has been easier to observe in authoritarian political regimes, but it has also existed in democratic regimes. The communist period in Romania is a revealing example for the process of political indoctrination in state schools and the mechanisms that made this possible. Nowadays, internal regulations of schools and universities, but also normative acts, prohibit political propaganda in educational institutions. But are they really respected? In a constantly changing society, values also change or are replaced. Some values end up being reflected by party ideologies. On the other hand, considering the fact that we live and function, since birth, in an ideological society, is it possible for us to get out of this paradigm and get rid of political propaganda in the educational process?